2004
DOI: 10.2118/88362-pa
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Phase Behavior and Numerical Dispersion in Finite-Difference Compositional Simulation

Abstract: Compositional simulation of multicontact miscible (or nearmiscible) gas injection problems is typically performed by use of numerical finite-difference (FD) schemes. Such simulations are intrinsically affected by numerical dispersion.* In this paper, we propose a method to assess the sensitivity of a particular displacement calculation to the effects of numerical dispersion for systems with realistic multicomponent fluid descriptions. We use two simple ternary systems to illustrate how dispersion and convectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 14 publications
4
33
0
Order By: Relevance
“…In other words, the use of coarser grids while underpredicting recoveries in 1D, could overpredict recoveries in multi-dimensions. Jessen et al [15] reported consistent findings. In 2D areal displacements, the coarser grids predicted higher recoveries despite the lower recoveries observed in 1D.…”
Section: Numerical Dispersion In Compositional Gas Simulationsmentioning
confidence: 72%
See 4 more Smart Citations
“…In other words, the use of coarser grids while underpredicting recoveries in 1D, could overpredict recoveries in multi-dimensions. Jessen et al [15] reported consistent findings. In 2D areal displacements, the coarser grids predicted higher recoveries despite the lower recoveries observed in 1D.…”
Section: Numerical Dispersion In Compositional Gas Simulationsmentioning
confidence: 72%
“…In 2D areal displacements, the coarser grids predicted higher recoveries despite the lower recoveries observed in 1D. Numerical dispersion leads to an improved sweep due to the suppression of preferential flow paths [15]. In summary, due to the interplay between numerical dispersion effects, which determine local displacement efficiencies, and viscous and gravity forces, which determine sweep efficiencies, the need to use fine grids to reasonably predict recoveries of miscible gas injection is problem dependent.…”
Section: Numerical Dispersion In Compositional Gas Simulationsmentioning
confidence: 98%
See 3 more Smart Citations